Baseline risk, timing of invasive strategy and guideline compliance in NSTEMI: Nationwide analysis from MINAP. (15th February 2020) - Rashid, Muhammad; Curzen, Nick; Kinnaird, Tim; Lawson, Claire A.; Myint, Phyo K.; Kontopantelis, Evangelos; Mohamed, Mohamed O.; Shoaib, Ahmad; Gale, Chris P.; Timmis, Adam; Mamas, Mamas A.
Abstract: Background: International guidelines recommend that for NSTEMI, the timing of invasive strategy (IS) is a function of patient's baseline risk. The extent to which this is delivered across and within healthcare systems is unknown. Methods: Data were derived from 137, 265 patients admitted with an NSTEMI diagnosis between 2010 and 2015 in England and Wales. Patients were stratified into low, intermediate and high-risk in keeping with international guidelines. Time to IS was categorised into early (24 h), intermediate (25–72 h) and late (>72 h). Multivariable logistic regression models were used to identify independent predictors of guidelines recommended receipt of IS. Results: There were 3608 (2.6%) low, 5037 (3.7%) intermediate and 128, 621 (93.7%) high-risk patients. Guidelines recommended use of IS was significantly lower in high-risk (16.4%) compared to intermediate (64.7%) and low-risk (62.5%) groups. Both men and women in the low-risk category were almost twice as likely to receive early IS compared to high-risk men (28.9% vs 17%, p < 0.001) and women (26.9% vs 15%, p < 0.001). Women (OR 0.91 95%CI 0.88–0.94), troponin elevation (OR 0.39 95%CI 0.36–0.43) and acute heart failure on admission (OR 0.65 95%CI 0.61–0.70) were strong negative predictors of receiving IS within recommended time in the high-risk group. Conclusion: Our study shows that IS for management of NSTEMI is not delivered according to international guidelines recommendations. Specifically, the disconnect between baseline risk and utility of IS increases with increasing risk and women achieve slower access than men to IS. Graphical abstract: Summary of main findings of the study. Unlabelled Image Highlights: Invasive strategy in the management of patients admitted with NSTEMI is guided by their baseline risk. Based on risk criteria of two international guidelines, over 90% of patients admitted with diagnosis of NSTEMI are high-risk. Only one in ten of these high-risk patients received invasive strategy within the recommended time. Paradoxically, both men and women with low-risk are twice as likely to receive early invasive strategy compared to high-risk men and women.